Sentiment Analysis of Twitter Data Using Text Classification And Clustering - Sinha, Kumari Ashmita; VKP, Maanasa; SP, Nikhitha; S, Ramya; CN, Mangala (International Journal of Computer Sciences and Engineering, 2025)
Information and data has always been consideredas the lifeline to run any business. The stability of an organization, the growth of the business, the profit gained or the loss suffered, all these factors depend on the information gained about the market trends and also most importantly public opinion. The sentiments of the people are therefore considered as the most crucial data that the organizations use in order to take effective decisions with minimum risk.In this paper we gather data from a type of social media that is twitter. This is because the public nowadays express their opinions and their feedbacks largely to through social media. In this paper we attempt to perform sentiment analysis using text classification by Naïve Bayes and text Clustering by K-means.